2022
DOI: 10.1007/s12035-022-03043-7
|View full text |Cite
|
Sign up to set email alerts
|

Dorsoventral Arrangement of Lateral Hypothalamus Populations in the Mouse Hypothalamus: a Prosomeric Genoarchitectonic Analysis

Abstract: The lateral hypothalamus (LH) has a heterogeneous cytoarchitectonic organization that has not been elucidated in detail. In this work, we analyzed within the framework of the prosomeric model the differential expression pattern of 59 molecular markers along the ventrodorsal dimension of the medial forebrain bundle in the mouse, considering basal and alar plate subregions of the LH. We found five basal (LH1–LH5) and four alar (LH6–LH9) molecularly distinct sectors of the LH with neuronal cell groups that correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 187 publications
0
9
0
Order By: Relevance
“…Finally, the subthalamic nucleus (originally lumped together with the pallidal primordia by Spatz, 1921, 1924, 1925) became dissociated from the hypothalamic entopeduncular population, once it was discovered that the former primordium is produced in the retromamillary basal plate region (within the hp1 prosomere of Puelles et al, 2012; this area is identified by columnar authors as ‘supramamillary area’). The subthalamic primordium migrates tangentially dorsalward under the pial surface of the peduncular hypothalamus into its dorsal retrotuberal final position (secondarily covered by the cerebral peduncle), as was concluded from descriptive data (Gilbert, 1935; Papez, 1940; Jiao et al, 2000), and confirmed experimentally by autoradiographic (Altman & Bayer 1986; Keyser, 1972; Marchand et al, 1986) and molecular analysis (Martin et al, 2002, 2004; Puelles et al, 2012; see also Diaz et al, 2023; López‐González et al, 2021; Puelles & Rubenstein, 2015).…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Finally, the subthalamic nucleus (originally lumped together with the pallidal primordia by Spatz, 1921, 1924, 1925) became dissociated from the hypothalamic entopeduncular population, once it was discovered that the former primordium is produced in the retromamillary basal plate region (within the hp1 prosomere of Puelles et al, 2012; this area is identified by columnar authors as ‘supramamillary area’). The subthalamic primordium migrates tangentially dorsalward under the pial surface of the peduncular hypothalamus into its dorsal retrotuberal final position (secondarily covered by the cerebral peduncle), as was concluded from descriptive data (Gilbert, 1935; Papez, 1940; Jiao et al, 2000), and confirmed experimentally by autoradiographic (Altman & Bayer 1986; Keyser, 1972; Marchand et al, 1986) and molecular analysis (Martin et al, 2002, 2004; Puelles et al, 2012; see also Diaz et al, 2023; López‐González et al, 2021; Puelles & Rubenstein, 2015).…”
Section: Introductionmentioning
confidence: 62%
“…Several other mRNA transcripts typically characterizing the EPV include the transcription factors Arx , Foxp2 , and Meis1 and other genes such as Cbln2 , Chrm3 , Pvalb , Trpc4 , Rgs4 , and Spp1 (Figure 2a,b; Table 3). The EPV is typically aligned dorsoventrally within the Dlx ‐positive subparaventricular band (in longitudinal continuity with the recently defined rostral liminar nucleus [RLi] of the prethalamus, which is also Dlx5/6 ‐ LacZ positive; Díaz et al., 2023; Puelles et al., 2021; EPV, RLi; Figure 1a). The peduncular position of EPV typically coincides roughly with the subpial course of the optic tract (ot; Figures 1c and 3) and is somewhat dorsal relative to the STh in the underlying basal plate (Figures 1b–d and 2b,k) and ventral to its alar companion, the EPD (the optic tract is thus useful for the distinction of the neighboring EPV and EPD formations).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations